Pelatihan Penyusunan Laporan Keuangan Bagi Umkm Handcraft Sukabumi - Nugroho, Gatot Wahyu (PT. Alahyan Publisher Sukabumi, 2023)
Financial statement preparation training is one solution to the problems faced by Handcraft Sukabumi MSMEs, namely the lack of knowledge related to the preparation of financial statements regarding balance sheets, working capital, profit and loss, changes in capital, and cash flow. The purpose of this activity is to improve participants' knowledge and skills in preparing financial statements. The method of implementing this activity is training for MSMEs Hancraft Sukabumi, Tangkil Village, Cidahu District, Sukabumi Regency. The partner of this training activity is MSME Handcraft Sukabumi. Evaluation of activities was carried out by giving questionnaires to trainees before and after delivering the material, and the result was that participants' knowledge and skills increased by 36%.